2020
DOI: 10.1155/2020/6975646
|View full text |Cite
|
Sign up to set email alerts
|

Preventive Effects of Chrysanthemum coronarium L. Extract on Bone Metabolism In Vitro and In Vivo

Abstract: Osteoporosis is characterized by decreased bone mass and bone microarchitectural failure, leading to an enhanced risk of bone fractures. Chrysanthemum coronarium L. (CC) is a natural plant with powerful antioxidant activity. This study investigated the antiosteoporotic effects of CC extracts in in vitro cell cultures and in vivo bone loss animal models. CC stimulated osteoblast differentiation and mineralized bone formation by osteoblasts by increasing the expression of bone formation markers (alkaline phospha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 48 publications
2
12
0
Order By: Relevance
“…In contrast, CCC may act as growth retardants and thereby inhibited biochemical processes resulting in less spreading of plants. The findings agree with those of Joshi et al [24] and Kim et al [25] in Chrysanthemum and Thu et al [26] in carnation . The variation in number of leaf production was pronounced by the application of different growth regulators.…”
Section: Effect Of Plant Growth Regulators On Plant Characteristics I...supporting
confidence: 93%
See 3 more Smart Citations
“…In contrast, CCC may act as growth retardants and thereby inhibited biochemical processes resulting in less spreading of plants. The findings agree with those of Joshi et al [24] and Kim et al [25] in Chrysanthemum and Thu et al [26] in carnation . The variation in number of leaf production was pronounced by the application of different growth regulators.…”
Section: Effect Of Plant Growth Regulators On Plant Characteristics I...supporting
confidence: 93%
“…The highest number of flower (40) was recorded with 150 ppm GA 3 , which was significantly superior to those observed by spraying 100 ppm GA 3 and 50 ppm GA 3 . Application of 800 ppm CCC produced minimum number of flowers (25) per pot, which was at par with 600 ppm CCC (27) and 400 ppm CCC (31). This was in line with the findings of Kim et al [25].…”
Section: Effect Of Growth Regulators On the Production Of Flower In C...mentioning
confidence: 93%
See 2 more Smart Citations
“…Similarly, we previously found the preventive effects of CC on bone metabolism in vitro and in vivo 9 . In addition, we recently showed that CC protects against premature senescence in vitro 10 .…”
Section: Introductionsupporting
confidence: 72%